2020
DOI: 10.1177/0890334420948451
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding but not Exclusively: Exploration of Chinese American Mothers’ Infant Feeding Practices

Abstract: Background Previous qualitative researchers have shown that Chinese American mothers experienced high rates of suboptimal breastfeeding, especially early introduction of other foods before the recommended 6-month period of exclusive breastfeeding. Research aims (1) To explore attitudes that Chinese American mothers have about the meaning and practice of exclusive breastfeeding; (2) to evaluate the extent of family pressure and support to maintain exclusive breastfeeding; and (3) to examine the influence of bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…In Group 1, the maternal intention was the strongest factor influencing longer breastfeeding duration, followed by self-efficacy and social support. Our findings are consistent with prior research that has linked these variables to longer breastfeeding periods (Goldbort et al, 2021 ; Granberg et al, 2020 ; Kronborg & Foverskov, 2020 ; Maleki-Saghooni et al, 2020 ; Wallenborn et al, 2019 ). In addition, Zarshenas et al ( 2020 ) found that introducing formula feeding before the age of 6 months is associated with early discontinuation of breastfeeding.…”
Section: Discussionsupporting
confidence: 93%
“…In Group 1, the maternal intention was the strongest factor influencing longer breastfeeding duration, followed by self-efficacy and social support. Our findings are consistent with prior research that has linked these variables to longer breastfeeding periods (Goldbort et al, 2021 ; Granberg et al, 2020 ; Kronborg & Foverskov, 2020 ; Maleki-Saghooni et al, 2020 ; Wallenborn et al, 2019 ). In addition, Zarshenas et al ( 2020 ) found that introducing formula feeding before the age of 6 months is associated with early discontinuation of breastfeeding.…”
Section: Discussionsupporting
confidence: 93%
“…Delphi methods to address problems related to breastfeeding Int J Public Health Sci ISSN: 2252-8806  Model development of early breastfeeding initiation and exclusive preparation (Nelly Indrasari) 551 maternal behavior [17]. Secondary data analysis of Health Demographic Survey to determine the combined prevalence of EBI, the big picture of the phenomenon of EBI administration, and the relationship of the place of birth with EBI [18]- [20]. Support from social connections, a crucial element in social interactions, can be categorized broadly into four types: emotional (including empathy, affection, trust, and concern), practical (material assistance and direct services that aid someone in need), informative (guidance, recommendations, and knowledge used to tackle issues), and evaluative.…”
Section: Introductionmentioning
confidence: 99%